Workaholism in law firms: dimensions and predictors = Workaholism na advocacia: dimensões e preditores = - Cruz, Sofia Alexandra (2022)
This article analyses workaholism in Portuguese corporate law firms, seeking to measure this phenomenon through the Work Addiction Risk Test (wart) - a self-assessment tool on dimensions related to compulsive tendencies, lack of control, impaired communication and self-absorption, inability to delegate and self-esteem. It is based on a survey applied to a convenience sample of corporate lawyers. The study shows the lack of control and compulsive tendencies contribute to explaining the phenomenon under discussion. It can be concluded through regression analysis that the position held, time at the office and working hours contribute as predictors for workaholism.